Marinatos, Nanno (2019). La Diosa del Sol y la realeza en la Antigua Creta. /Traducción: Amaya Bozal. Madrid: Machado, 334 págs. ISBN: 9788477743316 - Alfaro, Juan Pablo (2020)
Fil: Alfaro, Juan Pablo. Pontificia Universidad Católica Argentina; Argentina